MANAJEMEN IMPLEMENTASI HASIL BOS KINERJA JENJANG SD DI KECAMATAN PUGUNG - Sari, Rima Puspita; Aswad, Fatqul Hajar; Hendrowati, Tri Yuni; Siswoyo (Institut Ummul Quro Al-Islami Bogor, 2026)
This study aims to analyze the management of School Operational Assistance (BOS) Performance funds at the elementary school level in Pugung District, covering planning, organizing, implementation, supervision, and solutions to challenges faced by schools. The study employed a qualitative descriptive approach using interviews, observations, and documentation techniques at elementary schools receiving BOS Performance funds in 2025. The research informants consisted of principals, BOS treasurers, teachers, school operators, and school committee members. The findings indicate that the management of BOS Performance funds has been implemented effectively. In the planning aspect, schools involved all stakeholders in program preparation based on technical guidelines and school needs. The organizing aspect was reflected through clear task distribution, effective coordination, and good communication among stakeholders. In the implementation aspect, activities funded by BOS Performance were carried out according to the planned programs and supported the improvement of learning quality through teacher training and learning facility development. Supervision was conducted collectively through routine evaluations and the utilization of the ARKAS application to improve transparency and accountability in financial management. The obstacles faced by schools included limited reporting time, sudden changes in information from the education office, and administrative difficulties. The solutions implemented by schools included strengthening coordination, communication, and continuous evaluation